2002
DOI: 10.1046/j.1469-0705.2002.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Operative fetoscopy via telesurgery

Abstract: We describe a case in which telesurgical consultation from Tampa, Florida, USA was used to accomplish operative fetoscopy in Santiago, Chile for the treatment of a twin pregnancy involving an acardiac twin. The procedure was successful and a healthy infant was delivered at 37.5 weeks. Operative fetoscopy, a surgical approach to correct birth defects in utero via combined ultrasound and endoscopy, is only available in a handful of centers worldwide. Telesurgery makes use of telecommunication to allow a surgeon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
(6 reference statements)
0
16
0
3
Order By: Relevance
“…Early attempts were highly invasive and involved hysterotomy and removal of the acardiac twin [2,3,4]. Subsequently, a series of other less invasive intrauterine interventions aiming to arrest the circulation of the acardiac twin were introduced [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75]. These included insertion of cord coils, ligation with or without transection of the umbilical cord, endoscopic laser coagulation of placental anastomoses between the pump and acardiac twins, endoscopic laser coagulation and endoscopic or ultrasound-guided monopolar or bipolar diathermy of vessels within the cord supplying the acardiac twin and, more recently, ultrasound-guided ablation of intrafetal vessels by injection of alcohol, monopolar diathermy, laser or radiofrequency.…”
Section: Introductionmentioning
confidence: 99%
“…Early attempts were highly invasive and involved hysterotomy and removal of the acardiac twin [2,3,4]. Subsequently, a series of other less invasive intrauterine interventions aiming to arrest the circulation of the acardiac twin were introduced [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75]. These included insertion of cord coils, ligation with or without transection of the umbilical cord, endoscopic laser coagulation of placental anastomoses between the pump and acardiac twins, endoscopic laser coagulation and endoscopic or ultrasound-guided monopolar or bipolar diathermy of vessels within the cord supplying the acardiac twin and, more recently, ultrasound-guided ablation of intrafetal vessels by injection of alcohol, monopolar diathermy, laser or radiofrequency.…”
Section: Introductionmentioning
confidence: 99%
“…El cirujano remoto se guió en la gestión exitosa de un embarazo que implica un gemelo acárdico con ultrasonido transmitido, endoscopia e imágenes panorámicas de la sala de operaciones en tiempo real 37 . En otro proyecto entre Australia y Estados…”
Section: Ventajas Y Desventajas Del Uso De Tic En Obstetriciaunclassified
“…1 Telemedicine is a viable alternative for providing expert consultation and procedural guidance in rural and remote prehospital settings, [2][3][4][5][6] particularly in the fields of trauma and emergency medicine. 7,8 In 2010, Sakles et al 9 reported the first case of a remotely assisted tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%